Torastudium oder Militärdienst?: ein Diskurs bereits im Josuabuch - Gaß, Erasmus (Trierer theologische Zeitschrift, 2021)
The difficult question of “Torah studies or military service” is already addressed in the Book of Joshua. The different options are juxtaposed in Josh 1:1–9 without a clear decision which option is to be chosen. Obviously, Torah studies and military service be long together so that the Promised Land can be successfully conquered and permanently settled. However, the description of the conquest is increasingly demilitarised in the two editorial revisions that point to the Persian-Hellenistic period.